Clinico-epidemiological profiles of patients sustaining ocular trauma due to firecrackers during the festive season of Diwali - Joshi, Vasavi B.; Shastri, Manisha B.; Sheikh, Khushnood M. (International Journal of Research in Medical Sciences, 2017)
Background: Considerable number of cases of firecracker injuries is reported during the festive season of Diwali in India. The purpose of this study is to identify the clinico-epidemiological patterns of ocular injuries caused by firecrackers during this period. Methods: This was a prospective case series of patients attending eye OPD with ocular trauma sustained by Firecrackers during the festive season of Diwali, 2016 in a Tertiary Care Centre in Surat. Demographic data of all the patients and type of firecracker causing injury were noted. Ocular examination of all patients was performed at the time of presentation and on follow-up. Treatment received by the patients was noted. Results: Out of total 20 patients, 85% were male (17 out of 20). Mean age of the patients was 12.15 years and majority of patients (45%) were of 6 to 10 years’ age group. Most patients (85%) sustained injury by Single shot crackers like Bijili crackers and Timing bombs. The injuries reported ranged from Eyelid burns, conjunctival or corneal burns to partial thickness corneal tear and macular scar formation with interventions ranging from ocular wash with saline to repair of partial thickness corneal tear. Many of the injuries were caused because of negligence. Corneal epithelial defect was the most frequent injury (affecting 96% of the total no. of eyes affected) followed by Eyelid burns (affecting 56% of the total no. of eyes affected). Cases having visual impairment or blindness had corneal and/or retinal involvement. Conclusions: Ocular trauma resulting from firecrackers can lead to significant ocular morbidity and permanent blindness and is a preventable cause. All steps must be taken through public awareness and legislation to ensure that firecrackers are used in a safe manner during Diwali celebrations. The medical professionals should be adequately trained to give primary emergency care which has a key role in the visual outcome.